"Christianity. Fundamental Teachings" by the Churches in Turkey as an Example of an Ecumenical Catechism - Pawłowski, Sławomir (Verbum Vitae, 2022)
The booklet entitled Christianity. Fundamental Teachings, published by the Joint Commission of Churches in Turkey in 2018, expresses the shared beliefs of the Christian Churches in Turkey. It can be seen as a landmark in inter-church efforts to draw closer together. Trying to explain Christianity to non- Christians, the booklet presents the key elements of the Christian faith in a clear and easily comprehensible way. This article provides a synthetic presentation of the content of this booklet and shows issues that are important in the Turkish context. Since the call for “an ecumenical catechism” resonates from time to time in the international and inter-church areas, this joint publication of the Churches in Turkey can be a good example of such a catechism for other Churches worldwide. Moreover, this booklet can serve as a good teaching tool for Christians or non-Christians. Thus it is worth studying, translating, commenting on and implementing after being appropriately adjusted to other social, cultural and religious contexts.